Influência da fase de desenvolvimento sobre a toxicidade de Senna occidentalis e Senna obtusifolia para bovinos - Schenkel, Diego Montagner (2017)
Senna occidentalis and S. obtusifolia are poisonous plants for animals that toxic degenerative myopathy. Although S. occidentalis is believed to be more toxic than S. obtusifolia, there are no studies comparing the toxicity of these plants to cattle. For this purpose, 11 cattle were divided into 3 groups as follows: Group 1: composed of three cattle, two of which received leaves of S. obtusifolia and one of S. occidentalis; Group 2: formed by five cattle where four animals received pods of S. obtusifolia and one of S. occidentalis; And Group 3 was composed of three cattle where two of which received deeds of S. obtusifolia and one of S. occidentalis. The toxicity of each plant was compared according to the development phase as well as the toxicity among the species of Senna spp. Based on the clinical and morphological findings, the most toxic parts of each plant, as well as the toxicity of each were determined.